PENERAPAN STRATEGI PEMBELAJARAN AKTIF JEOPARDY REVIEW UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR KIMIA PESERTA DIDIK PADA POKOK BAHASAN KOLOID DI KELAS XI MIA 7 MAN 2 MODEL PEKANBARU - Udlhiati, Imas; Rasmiwetti, Rasmiwetti; Susilawati, Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The aim of this research was to improve the student activity andachievement used active learning strategy Jeopardy Review on the subject of colloid inclass XI science 7 MAN 2 Model Pekanbaru. This research was conducted in twocycle. Each cycle consisted of two meetings. Learning activity data is collected byobservation sheet and learning result data is collected by test. The analysis data wasdescrib with descriptively. The result of action showed that learning activity percentageof student improved and reached the success criteria. The learning activity of studentpercentage in first cycle was 56,35% with enough category and the second cycle was69,90% with good category. Student learning activities are good in line with thelearning outcomes obtained by student. Student achievement was seen from masterylearning that enhances and have achieved success criteria. The percentage of studentachievement in the first cycle was 73,08% and the second cycle was 88,46%. Based onthe results obtained, it can be concluded that using active learning strategy jeopardyreview can improve the activity and student achievement.Keyword: Active learning strategy Jeopardy Review, student learning activity, student achievement, colloid